Safety limits of antidepressant use plus combinations: Focus on cardiovascular function - Stella, Florindo [UNESP]; Loureiro, Júlia C.; Pais, Marcos V.; Canineu, Paulo R.; Forlenza, Orestes V. (Bentham Science Publishers, 2018)
Background: Antidepressants have been widely prescribed for depression, anxiety, sleep disorders, and in the management of behavioural symptoms of adult-old patients. Although generally safe, newer generation antidepressants are not devoid of the risk of inducing clinically relevant adverse events. Objectives: To investigate the association between newer generation antidepressants and the occurrence of cardiovascular adverse events and electrocardiogram (ECG) abnormalities. Method: Studies were included in the review according to the following criteria: a) clinical trials (placebo-controlled or not) or case reports; b) short- or long-term interventions with antidepressants; c) prescription of newer generation antidepressants as first-line treatment; d) samples of adult or adult-old patients. From a total of 301 articles addressing the association between antidepressants and cardiovascular adverse events as primary or secondary outcomes, we selected 30 controlled clinical trials and 10 case reports. Results: In most clinical studies, the effects of antidepressants on cardiac function are usually computed as secondary outcome variables, however with limited information. Conversely, case reports tend to present more comprehensive sets of clinical and laboratorial parameters, but the generalization of such data is limited by the small number of observations. The occurrence of QTc prolongation (with increased risk of torsade de pointes) has been reported. Aging, higher dosages of antidepressants, drug interaction, and pre-existing cardiovascular comorbidities were found as risk factors for the aforementioned cardiovascular and ECG abnormalities. Conclusion: Prescribing antidepressants requires caution given their potential impact on cardiac function, and the clinician should carefully monitor cardiovascular and ECG parameters particularly in cases with underlying heart disease.
Keywords: Adult-old patients; Aging; Antidepressants; Cardiovascular disorders; ECG abnormalities; QTc prolongation